2021
DOI: 10.1016/j.eats.2020.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using Bone–Patellar Tendon–Bone Autograft With Suture Tape Augmentation

Abstract: The anterior cruciate ligament (ACL) is the most commonly injured ligament in the knee, with injury usually occurring as a result of multidirectional sports. The incidence of ACL injury has continued to increase, with most patients opting for surgery to improve stability as well as permit a return to sport. Traditional methods of ACL reconstruction can achieve this but are not without their problems, including graft rupture, residual laxity, and donor-site morbidity. There is therefore a requirement for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…They exhibit good mechanical properties and biocompatibility. [29][30][31][32][33] The CKT is a braided technique of suture line that only relies on hand-knitting to adjust the ductility and elasticity of the suture line. When the length of each knot is 3 mm, the ductility and elasticity of the braided suture line were similar with the hamstring tendon.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit good mechanical properties and biocompatibility. [29][30][31][32][33] The CKT is a braided technique of suture line that only relies on hand-knitting to adjust the ductility and elasticity of the suture line. When the length of each knot is 3 mm, the ductility and elasticity of the braided suture line were similar with the hamstring tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Benson et al. 19 described ACLR with bone patellar tendon bone autograft augmented with suture tape. The tape was fixed independently using SwiveLock knotless anchor distal to tibial tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopic analyses showed that glycerol formed a coating on the collagen fibers, without altering their three-dimensional organization (data not shown). Additionally, the interesting work of Benson et al [ 43 ] demonstrated that a suture tape augmentation acted as a stabilizer during the early stages of the graft incorporation.…”
Section: Discussionmentioning
confidence: 99%